(untitled) (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazione SOMMARIO: 1. Due forme di giustificazionismo: inclusivo ed esclusivo - 2. Il giustificazionismo moderato di Gerald Gaus - 3. Il principio di motivazione secolare e le problematiche operative - 4. Due modelli a confronto: convergenza vs. consensus - 5. Verso una formulazione minimal del proviso di giustificazione - 6. Alcune notazioni critiche: la sovrapposizione tra i concetti di motivo e ragione e il fraintendimento sull’overlapping consensus - 7. Giustificazionismo eaccomodation: possibili implicazioni? Abstract: According to the justificatory liberalism view, to respect each citizen as free and equal requires that no one simply be forced to submit to the judgments of others; then is necessary laws must be justified to those subject by reasons that everyone could share. There are two different perspectives: justificatory liberalism inclusive andjustificatory liberalism exclusive; only for the second view is not binding to expunge religious-based reasoning from political justification. Gerald Gaus claims that the model of consensus is based on a misleading intepretation of the overlapping consensus conception: "because we cannot reasonably expect all members of the public to actually endorse religious reasons as good reasons, they are not justificatoryreasons". Gaus define a conceptual political system inspired to the possibilities of convergence and also try to challenge the standard formulation of the liberal proviso by offering a miminalist reformulation of the translation clause. The paper analize and criticize this inclusive model of justificatory liberalism.